Mémoires de Mademoiselle de Montpensier : fille de Gaston d'Orléans, frere de Louis XIII, roi de France. - Montpensier, Anne-Marie-Louise d'Orléans, duchesse de, 1627-1693. (Tufts University. Tisch Library., 2015)
Volume 3 of 8.; Nouvelle édition /où l'on a rempli les lacunes qui étoient dans les editions précédentes, corrigé un très-grand nombre de fautes, & ajouté divers ouvrages de Mademoiselle, très-curieux.; 1 online resource (8 volumes); Imprint varies: t. 3-8 have "Ph. Roux."; Title-page in red and black.; Head- and tail-pieces; initials.; Includes index.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.